2016
DOI: 10.22230/ijepl.2016v11n8a606
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of retention, expenditures, and class size on primary school completion in Sub-Saharan Africa: A cross-national analysis

Abstract: Education in Sub-Saharan Africa is increasingly viewed as a means of emancipation and a transformative project for social mobility. Developing nations have pursued policies such as universal or free primary education to increase access to education and improve student outcomes. In this study, direct and indirect precursors to primary school completion in Sub-Saharan Africa are analyzed using national cross-sectional data collected by the UNESCO Institute for Statistics. Results show that imbalanced pupil-teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…have been inconsistent (Michaelowa and Weber 2007;Richards and Vining 2015;Dreher et al 2008). An area where evidence is more mixed is the financing of education including domestic expenditures and foreign aid for education (Michaelowa and Weber 2007;Yogo 2017;d' Aiglepierre and Wagner 2013;Ruff 2016;Bruns et al 2003;Dreher et al 2008). In the studies where these measures are found to be significant, the effects are small which may be explained by the mediating role of governance; the impact is likely to be shaped by a nation's ability to spend dollars well and effectively.…”
Section: Control Variablesmentioning
confidence: 99%
“…have been inconsistent (Michaelowa and Weber 2007;Richards and Vining 2015;Dreher et al 2008). An area where evidence is more mixed is the financing of education including domestic expenditures and foreign aid for education (Michaelowa and Weber 2007;Yogo 2017;d' Aiglepierre and Wagner 2013;Ruff 2016;Bruns et al 2003;Dreher et al 2008). In the studies where these measures are found to be significant, the effects are small which may be explained by the mediating role of governance; the impact is likely to be shaped by a nation's ability to spend dollars well and effectively.…”
Section: Control Variablesmentioning
confidence: 99%